Herpetic Uveitis: An Experience from a Tertiary Referral Center in Bulgaria - Gueorgui Markov; Rozalia Hristova; Nikolina Andonova; Iva Petkova; Yani Zdravkov; Alexander Oscar (Sriwijaya Journal of Ophthalmology, 2022)
Introduction: The human Herpesviridae have been described as a leading cause of infectious uveitis. The most common manifestations are keratouveitis and iridocyclitis. The diagnosis is usually made on clinical grounds. The present therapy is based upon the inhibition of viral replication and the use of anti-inflammatory medications. Methods: A descriptive study was conducted on the records of 206 patients with uveitis from the Clinic of Ophthalmology at University Hospital Alexandrovska, Sofia, Bulgaria. The study period was from January 2012 until August 2019. The diagnosis was based on the clinical exam and, when necessary, on specialized testing – PCR on aqueous humor or vitreous material. We used descriptive statistical methods. Results: Out of 206 patients with intraocular inflammation, 46 (22.3%) were diagnosed with herpetic uveitis. Of them, 35 (76.1%) had anterior uveitis, 7 patients (15.2%) had panuveitis, and 4 patients (8.7%) had posterior uveitis. The mean age was 45.3 years. The leading complications were ocular hypertension, corneal leucoma, retinal detachment, and cataract. Antiviral therapy with acyclovir or valaciclovir, alone or with corticosteroids, was used in all groups. Conclusion: The herpesviruses are important causative agents of infectious uveitis. In our study, non-granulomatous, hypertensive anterior uveitis was the most common clinical entity. There were also a few patients with posterior and panuveitis. VZV was the most common etiologic agent. The panuveitis cohort had the worse prognosis for visual acuity, mostly as a result of retinal detachment. The posterior uveitis presented most frequently as focal retinochoroiditis with a good prognosis.